Naftopidil molecular salts with improved dissolution and permeation - Mannava, M. K. Chaitanya; Dandela, Rambabu; Tothadi, Srinu; Solomon, K. Anand; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
Naftopidil (NFPD) is a alpha 1 adrenoceptor antagonist drug. Low solubility and low permeability are the major drawbacks of this drug. The synthesis of multicomponent crystalline forms of this amine functional group drug with carboxylic acid coformers, both achiral and chiral acids, provides a solution to improve its solubility as well as permeability. Nine molecular salts were crystallized by liquid-assisted grinding followed by isothermal crystallization. Single-crystal X-ray diffraction analysis of the molecular salts showed that the structures are stabilized by strong N-H center dot center dot center dot O and O-H center dot center dot center dot O and weak C-H center dot center dot center dot O hydrogen bonds in the solid state. The bulk phase purity of new solid forms was confirmed by powder X-ray diffraction (PXRD), and the crystalline products were further characterized by IR spectroscopy and thermal analytical techniques (differential scanning calorimetry). The molecular salts exhibit superior dissolution rates compared to pure NFPD. However, during dissolution, NFPD showed decrease in concentration after 60 min for all salts due to precipitation. The supersaturation occurred due to salt disproportionation, which generates insoluble NFPD, as confirmed by PXRD of the residue. The salts reach high saturation concentration before 60 min, which is indicative of immediate release formulation to achieve fast onset of therapeutic activity. Moreover, the salts exhibit high saturation in phosphate buffer saline media and improved permeability compared to the pure drug. Finally, the D,L-malic acid racemate of NFPD shows enhanced dissolution and permeability compared to all other salts and pure NFPD.

Novel pharmaceutical cocrystals and salts of bumetanide - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
New crystalline forms of bumetanide, namely, four cocrystals, two salts, and one salt-cocrystal were crystallized. Urea and lactams such as valerolactam, caprolactam, and N-methyl caprolactam formed cocrystals with bumetanide, whereas 4-aminopyridine gave a salt. Piperazine afforded a salt hydrate, and 5-fluorocytosine gave a salt-cocrystal. The supramolecular synthons in bumetanide-lactam cocrystals are an amide dimer between drug and coformer, and acid homo dimer between bumetanide molecules. In bumetanide salts, the acid proton is transferred from bumetanide to coformer amine, whereas in bumetanide salt-cocrystal proton transfer and free acid were observed in the crystal structure. Similarly, the cytosine salt-cocrystal of bumetanide and fluorocytosine also gave a salt-cocrystal adduct. The acid proton of bumetanide is transferred to the 2-amino pyridine base of cytosine as a salt, and on the other side of the drug molecule the sulfonamide interacts with the syn amide part of cytosine. Furthermore, solubility, dissolution, and diffusion membrane permeability experiments were performed on all new solid forms. The piperazine salt shows high dissolution and permeability crossover when compared to other binary forms of bumetanide.

Novel crystal forms of Entresto: a supramolecular complex of trisodium sacubitril/valsartan hemi-pentahydrate - Shaikh, Tabrez R.; George, Christy P.; Bhukya, Priyanka; Shelke, Nikita; Pawar, Komal; Garai, Abhijit; Dandela, Rambabu; Gonnade, Rajesh G.; Nangia, Ashwini K. (Crystengcomm, 2022)
Entresto is a salt-cocrystal supramolecular complex with the chemical name trisodium sacubitril/valsartan hemi-pentahydrate for treating chronic heart failure and was approved by the US FDA in 2015. This multidrug complex was synthesized in our laboratory to investigate its polymorphic behavior. Different crystallization conditions, including various solvent systems, yielded different novel solid forms of Entresto (Form-I to Form-VI), including the reported form. All the novel solids are solvent-dependent and were reproducibly crystallized on a 10 g scale quantity. The 1H NMR spectra confirmed the 1 : 1 stoichiometry of the two drugs, namely, sacubitril and valsartan, in all the solid forms of the crystalline products. Powder X-ray diffraction and DSC analysis of the crystalline solids established that they are distinct crystalline forms. Stability studies under ambient conditions carried out over a one-year period showed higher stability for Form-I and Form-III compared to the other forms, including the innovator crystal form (labelled as Form-II). The novel crystal forms (notably Form-I and Form-III) exhibit higher stability and less hygroscopicity than the reported Form-II.